Cutaneous adverse events in patients treated with BRAF inhibitor‐based therapies for metastatic melanoma for longer than 52 weeks. (1st January 2015) - Anforth, R.; Carlos, G.; Clements, A.; Kefford, R.; Fernandez‐Peñas, P.
Summary: Background: BRAF inhibitor‐based therapies have been shown to induce cutaneous toxicities, with onset generally in the first 8–26 weeks of therapy. Objectives: To determine whether cutaneous toxicities persist in patients who have remained on BRAF inhibitor‐based therapies for longer than 52 weeks, and therefore whether ongoing dermatology assessment is required. Methods: All patients treated with the BRAF inhibitors vemurafenib or dabrafenib or combination BRAF inhibitor and mitogen‐activated protein kinase kinase (MEK) inhibitor therapy at Westmead Hospital, Sydney, Australia underwent regular dermatological assessments for the duration of therapy. All patients enrolled in a clinical trial, and 18% of patients in the compassionate access scheme underwent a baseline assessment prior to commencement of therapy and every 4–8 weeks thereafter. Patients' adverse events were recorded in a specific database. Results: Patients continued to develop cutaneous adverse events after 52 weeks of continuous therapy. Patients on single‐agent BRAF inhibitor therapy suffered from Grover disease (45%), plantar hyperkeratosis (45%), verrucal keratosis (18%) and even cutaneous squamous cell carcinoma (16%). The most frequent adverse event seen in patients in the combination BRAF and MEK inhibitor group was an acneiform eruption (40%). Conclusions: Patients on BRAF inhibitor‐based therapies need to continue to have regular dermatological follow‐up independent of the duration of their therapy.